2016
DOI: 10.3352/jeehp.2016.13.38
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles, academic achievement, and mental health problems among medical students in Thailand

Abstract: PurposeThis study aimed to investigate the prevalence of various learning styles among medical students and their correlations with academic achievement and mental health problems in these students.MethodsThis study was conducted among 140 first-year medical students of Chiang Mai University, Thailand in 2014. The participants completed the visual-aural-read/write-kinesthetic (VARK) questionnaire, the results of which can be categorized into 4 modes, corresponding to how many of the 4 types are preferred by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
0
20
1
1
Order By: Relevance
“…This is similar to the observation from the Al-Saud’s study and the study by Nuzhat et al 29 of medical students, which found multimodal learning to be associated with a higher GPA among the surveyed students. However, no such association was found among medical students in Almigbal’s 25 and Paiboonsithiwong et al 17 studies. Similar to the medical curriculum, the dental curriculum also includes didactics but is traditionally much more centered on manual and practical proficiencies, areas where a multimodal learning style may position students with this preference at an advantage over other peers.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is similar to the observation from the Al-Saud’s study and the study by Nuzhat et al 29 of medical students, which found multimodal learning to be associated with a higher GPA among the surveyed students. However, no such association was found among medical students in Almigbal’s 25 and Paiboonsithiwong et al 17 studies. Similar to the medical curriculum, the dental curriculum also includes didactics but is traditionally much more centered on manual and practical proficiencies, areas where a multimodal learning style may position students with this preference at an advantage over other peers.…”
Section: Discussionmentioning
confidence: 86%
“…There is a relative abundance of studies looking at the different learning styles in variable fields of study such as medicine, 17 , 18 engineering, 19 nursing, 20 and allied health spe-cialties. 21 Existing studies examining VARK learning preferences among dental students are few with some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…(15) Paiboonsithiwong's study showed that the most preferred VARK learning style among medical students was quadmodal. (17) The reasons for the difference among bachelor degree nursing students and associate degree nursing students may be multifactorial. Differences may be mainly attributed to the fact that both undergraduate and associate degree nursing students had made adjustments in their own learning styles in the teaching process to adapt to the teaching environment and Comparison of VARK subcategories among bachelor degree and associate degree nursing students teaching style.…”
Section: Discussionmentioning
confidence: 99%
“…Paiboonsithiwong and colleagues surveyed 140 first-year medical students and found that medical students with a kinesthetic learning preference had lower GPAs in the first semester, but found no other differences among learning preferences, including in second semester GPA. 24 They also found no differences between VARK preference and Perceived Stress Scale score. 24 None of the identified studies described how learners used the results to increase their self-awareness.…”
Section: Resultsmentioning
confidence: 93%
“…[19][20][21][22] The two studies that found a significant correlation between a VARK preference and a learning outcome were conducted by Kim and Gilbert and Paiboonsithiwong and colleagues. 23,24 Kim and Gilbert surveyed 62 applicants to a general surgery residency program and found that medical students with an aural learning preference performed better on the United States Medical Licensing Examination Step 1 and Step 2 compared with medical students with a kinesthetic or multimodal learning preference. 23 Additionally, they found that those with a visual preference had higher Step 1 scores than those with a kinesthetic preference.…”
Section: Resultsmentioning
confidence: 99%